The Rumah Quran as an Alternative to Islamic Boarding School-style Education for Housewives: (Community-Based Research) - Ahmad Zaky; Tiy Kusmarrabbi Karo; Muhammad Syarif Muda Hasibuan; Wagiman Manik; Khairul Anhar (As-sunnah: Jurnal Pengabdian Masyarakat, 2022)
The Rumah Quran is a center and alternative for studying religious sciences that are not based on Islamic boarding schools and non-formal education for all groups, both children and housewives and housewives and housewives, teenagers to adults, this article will explain or summarize the activities held in the house of the Quran for housewives who have minimal time to study religion. Because they have minimal time to study Islam, effective religious activities are made for housewives so that they can study Islamic religious knowledge even though they have minimal time. The method used in this community service article is CBR (community-based research) in which researchers carry out activities in collaboration with the community, namely through intermediaries at the Koran house in the community and socializing activities together with teachers at the Al-Fatah Quran house. . The activities that have been carried out have advantages and have a positive impact on housewives at the Al-Fatah Qur'an House, this can be seen from their reading of the Qur'an which has improved from before, the enthusiasm to study religious knowledge some even have the opportunity to learn Arabic.